Identification by Inverse Virtual Screening of magnolol-based scaffold as new tankyrase-2 inhibitors. Issue 14 (7th August 2018) - Di Micco, Simone; Pulvirenti, Luana; Bruno, Ines; Terracciano, Stefania; Russo, Alessandra; Vaccaro, Maria C.; Ruggiero, Dafne; Muccilli, Vera; Cardullo, Nunzio; Tringali, Corrado; Riccio, Raffaele; Bifulco, Giuseppe
Graphical abstract: Abstract: The natural product magnolol (1 ) and a selection of its bioinspired derivatives 2 –5, were investigated by Inverse Virtual Screening in order to identify putative biological targets from a panel of 308 proteins involved in cancer processes. By this in silico analysis we selected tankyrase-2 (TNKS2), casein kinase 2 (CK2) and bromodomain 9 (Brd9) as potential targets for experimental evaluations. The Surface Plasmon Resonance assay revealed that 3 –5 present a good affinity for tankyrase-2, and, in particular, 3 showed an antiproliferative activity on A549 cells higher than the well-known tankyrase-2 inhibitor XAV939 used as reference compound.